The comparison of cointegration methods applications of Lithuanian’s economy modeling results - Firkovič, Viktorija; Rudzkis, Rimantas (Lietuvos matematikos rinkinys, 2003)
Actual goal in the modeling of the Lithuania’s transition economy is to compare some different analysismethods of cointegrated time series: Johansen’s, Box–Tiao, Stock–Watson, Engle–Granger two step procedure and principal components analysis. We investigate mathematical models of the long-run relations and changes of macroeconomic indicators, which we statistically identify using different statistical estimator of cointegrated vectors (CI) and vector error correction model (VECM).